Brain atrophy in the visual cortex and thalamus induced by severe stress in animal model. Issue 1 (December 2017) - Yoshii, Takanobu; Oishi, Naoya; Ikoma, Kazuya; Nishimura, Isao; Sakai, Yuki; Matsuda, Kenichi; Yamada, Shunji; Tanaka, Masaki; Kawata, Mitsuhiro; Narumoto, Jin; Fukui, Kenji
Abstract Psychological stress induces many diseases including post-traumatic stress disorder (PTSD); however, the causal relationship between stress and brain atrophy has not been clarified. Applying single-prolonged stress (SPS) to explore the global effect of severe stress, we performed brain magnetic resonance imaging (MRI) acquisition and Voxel-based morphometry (VBM). Significant atrophy was detected in the bilateral thalamus and right visual cortex. Fluorescent immunohistochemistry for Iba-1 as the marker of activated microglia indicates regional microglial activation as stress-reaction in these atrophic areas. These data certify the impact of severe psychological stress on the atrophy of the visual cortex and the thalamus. Unexpectedly, these results are similar to chronic neuropathic pain rather than PTSD clinical research. We believe that some sensitisation mechanism from severe stress-induced atrophy in the visual cortex and thalamus, and the functional defect of the visual system may be a potential therapeutic target for stress-related diseases.